Does disaster strike only when the Lord sends it? Prophetic eschatology and the origin of evil in Amos 3:6 - Bosman, Hendrik Ludolph (Old Testament essays, 1988)
Amos 3:6 is interpreted as part of 3:3-8 and is understood against the background of the eschatology of Amos. This paper concludes that Amos was not concerned with the ultimate origin of evil - that remains an enigmatic mystery.